Segunung Goes Digital: Application of Virtual Tour to Kampung Adat Segunung - A. Muammar Alawi; Arin Setiyowati; Praja Firdaus Nuryananda (Future Science, 2023)
Kampung Adat Segunung, is one of the fostered areas and the partners of the Faculty of Social and Political Sciences UPN